Can higher-proficiency L2 learners benefit from working with lower-proficiency partners in peer feedback?. Issue 2 (17th February 2017) - Yu, Shulin; Hu, Guangwei
ABSTRACT: Informed by Vygotsky's conceptualization of the Zone of Proximal Development, this case study investigated the benefits of peer feedback on second language (L2) writing for students with high L2 proficiency and the factors that may influence their learning in peer feedback in the Chinese English-as-a-foreign-language context. Specifically, the study examined whether, what, and how higher-proficiency (HP) English learners can learn when they collaborate with their lower-proficiency counterparts. Analyses of multiple sources of data – video-recordings of peer feedback sessions, interviews, stimulated recalls, and drafts of student texts – revealed that while group peer feedback in the writing classroom can provide learning opportunities for HP students, their learning can be influenced by several factors, including their beliefs about peer feedback, motives and goals for peer feedback, and medium of group discussion. Implications are drawn from these findings for peer feedback practice and research in L2 writing.